The TPACK Framework On Teacher’s Classroom Activity at Ma’Had Tahfidzul Qur’an Rahmatullah Samarinda - Wasilatun Abidah; Bibit Suhatmady; Effendi Limbong (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2018)
Indonesian students who are uninterested in English learning demands English teacher to be more creative and clever to choose an exact way in teaching. One of better ways is integrating various technologies into teacher’s teaching in any content area. In this case, TPACK framework is so needed to create an effective and efficient English teaching and learning that make students interested and motivated. As in MTQ Rahmatullah Samarinda, English teacher uses technology in teaching English. This study proposed 1) to investigate the TPACK being included in teacher’s lesson plan. 2) To analyze how the English teacher implementing TPACK framework in teaching. 3) To compose what problems are faced by teacher in teaching within the TPACK framework. The design of this study was a qualitative research, a case study. In this study, purposive sampling was chosen. From three classroom observations and one interview, this study revealed three findings: 1) the English teacher applied TPACK framework based on her lesson plan. 2) the English teacher applied TK, CK, PK, and PCK, TPK while did not apply TCK and TPACK based on her classroom observation and document finding. 3) there seven problems were faced by the English teacher in applying TPACK that was include of the difficulties in selecting best technology in efficient time (TK), mastering the topic especially pronunciation mistakes (CK), managing the classroom setting (PK), choosing a good way for receiving teacher’s goal with specific English material (PCK), creating an efficient time by using suitable technology to make students easier to understand and engage them (TCK), utilizing technologies to manage noisy classroom (TPK), and applying various technologies for specific subject content (TPACK). In short, based on the finding it showed that by applying TPACK the teacher required suitable technologies and methods in teaching to encourage students learning English